Embedding Character Values in Elementary School : The Key to Future Skills - Aulia Ihza Cahya; Dede Supriyanto; Sofyan Iskandar (Journal of Pedagogi, 2024)
Character education in primary schools is a crucial aspect in shaping quality generations, not only academically but also morally. This article aims to explore various dimensions of character education, including theoretical frameworks, successful models, and the challenges and opportunities in its implementation in Indonesia. Integrating character education with 21st-century skills such as creativity, collaboration, and communication is a primary focus, emphasizing the importance of a holistic approach to learning. Additionally, this article offers practical recommendations for linking character education with various teaching methods, including project-based learning, that involve collaboration between schools, parents, and the community. This research also reflects the novelty compared to previous literature, which often remains disconnected from practical contexts. By emphasizing the synergy among stakeholders, it is hoped that an environment supporting student character development can be created, allowing character education to become a key pillar in primary education in Indonesia.